MiniDES - Lightweight Python Simulation Framework for Interconnected Renewable Resources - Schlund, Jonas; Reisenweber, Julian; German, Reinhard (Proceedings of the IEEE Green Energy and Smart Systems Conference 2019, 2019)
Photovoltaic systems and battery storages are increasingly installed on distribution feeders. As the digitization of the grid evolves, collective control paradigms of distributed assets become possible. The proposed simulator MiniDES is a generic python framework to model and interconnect such distributed assets in flexible control scenarios and modular simulation setups. An integrated aggregator model allows for versatile queries, different state-dependent control setups as well as postprocessing all data obtained during simulation. The framework is available as open source, portable and offers a template with household scenarios to build upon. In addition, the simulator can easily be coupled with the electric power system simulator OpenDSS in order to include a power flow analysis. An exemplary case study collectively optimizes the inverter power of a 20 household community, each with a rooftop photovoltaic plant and a battery, and achieves loss savings of 33% as well as considerable increases in self-sufficiency in comparison to the individual control case. The according power flow analysis showed that the increased line losses caused by the increased grid utilization of the collective control case are negligible compared to the loss savings. In addition, our simulation shows that the beneficial community control is economically infeasible with a conventional price mechanism and that economic feasibility can be achieved by introducing a more dynamic price mechanis
Keywords: renewable energy; smart grid; simulation framework; solar power; energy storage; optimization